1972
DOI: 10.1155/tsm.1.157
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Rolling Texture of Iron Determined by Neutron‐Diffraction

Abstract: The development of the rolling texture of a low carbon steel was investigated by neutron diffraction calculating three-dimensional orientation distribution functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…More recent work using higher resolution techniques based on the orientation distribution functions (ODFs) has shown that ferritic stainless steel (Fe-10 pct-16 pct Cr) [7] and Fe 3 pct Si [8] produce rolling textures identical to those produced in low C and IF steels. [9] These results indicate that alloying different metallic elements that form bcc structures to the levels investigated does not produce texture modifications, which can be attributed to a lowering of their SFEs. However, no articles deal with bcc MgLi from a texture standpoint; thus, another approach is to consider the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…More recent work using higher resolution techniques based on the orientation distribution functions (ODFs) has shown that ferritic stainless steel (Fe-10 pct-16 pct Cr) [7] and Fe 3 pct Si [8] produce rolling textures identical to those produced in low C and IF steels. [9] These results indicate that alloying different metallic elements that form bcc structures to the levels investigated does not produce texture modifications, which can be attributed to a lowering of their SFEs. However, no articles deal with bcc MgLi from a texture standpoint; thus, another approach is to consider the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 72%
“…The ODFs and 200 pole figures for the as-received and annealed hot band are shown in Figures 1(b) and (c). Also included is a labeled / 2 45 deg section of BungeÕs [9] version of Euler space (Figure 1(d)). The a and c fibers are indicated.…”
Section: A Cold Rollingmentioning
confidence: 99%
“…: +34 91 624 8734; fax: +34 91 624 8749. temperature. In addition, ECAE deformation produces different textures [17,18], although somewhat weak and without stabilization, compared with that resulting by rolling [19,1]. After one pass ECAE the texture could approach the simple shear texture, where the shear plane is parallel to the P plane as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the iron texture will be described in each case as a limited fibre texture starting on (100)(110) (Schl/ifer and Bunge, 1974), silver shows a weak modified cube texture in samples at 10 and 30% silver contents (Figure 7). The Kurdjumov-Sachs relationship between iron and silver was discussed; it was also observed in Fe-Cu composites of this type.…”
Section: Introductionmentioning
confidence: 99%